Pemanfaatan Limbah Cair Tempe Untuk Kultur Chlorella sp. Sebagai Bahan Baku Biodiesel - Latif, Arya Zikri Maulana; Zahidah, Zahidah; Liviawaty, Evi; Herawati, Heti (SENTRI: Jurnal Riset Ilmiah, 2025)
The increasing demand for fossil fuel energy (BBM) has driven the development of renewable energy sources, one of which is biodiesel derived from microalgae. Chlorella sp. is a promising microalga due to its high lipid content. This study aims to determine the optimal concentration of tempeh wastewater for culturing Chlorella sp. to maximize lipid production as a raw material for biodiesel. The culture was carried out for five days using different treatments of tempeh wastewater: 0% (control using Walne fertilizer), 3%, 5%, 7%, and 9%. Observed parameters included temperature, pH, dissolved oxygen, nitrate, phosphate, cell density, and lipid content, with lipid extraction performed using the Soxhlet method. The culture temperature ranged from 25-27°C, pH increased from acidic to neutral, and dissolved oxygen levels decreased at higher wastewater concentrations. The highest cell density was found in the 7% treatment (8.45 million cells/mL), although it was not significantly different from the other treatments. The highest lipid content was obtained at 3% wastewater (40.3%), which was higher than the control (21.3%) and other treatments. The decrease in lipid content at higher wastewater concentrations was attributed to toxicity and reduced media quality. It is concluded that a 3% concentration of tempeh wastewater is optimal for enhancing lipid production in Chlorella sp. as a sustainable biodiesel feedstock.